Cetaceans of southern Peru: a review of recorded species - Santillán Corrales, Luis Alfredo (2021)
This article presents a review of cetacean species in the south coast of Peru between latitudes 16° and 18° LS. The information came from scientific papers, data obtained by the author and data shared by local biologists. The total number of species with a positive identification was 16, corresponding to 50% of the cetacean diversity registered in Peru. The majority of species (12) corresponded to toothed whales and for baleen whales the diversity was four species. Latitudes 16° and 17° harbor the majority of the species as well as the largest groups of toothed whales. That pattern is coincident with the continental shelf extension which is wider between the latitudes 16° and 17° LS influenced by the large coastal rivers at southern Arequipa.